Ireland's great famine and popular politics
1 online resource (viii, 240 pages)
Keywords: "Ireland's Great Famine of 1845-52 was among the most devastating food crises in modern history. A country of some eight-and-a-half-million people lost one million to hunger and disease and another million to emigration. According to land activist Michael Davitt, the starving made little or no effort to assert 'the animal's right to existence,' passively accepting their fate. But the poor did resist. In word and deed, they defied landlords, merchants and agents of the state: they rioted for food, opposed rent and rate collection, challenged the decisions of those controlling relief works, and scorned clergymen who attributed their suffering to the Almighty. The essays collected here examine the full range of resistance in the Great Famine, and illuminate how the crisis itself transformed popular politics. Contributors include distinguished scholars of modern Ireland and emerging historians and critics. This book is essential reading for students of modern Ireland, and the global history of collective action"--